Pengaruh Ketersediaan Obat dan Kualitas Pelayanan Farmasi terhadap Kepuasan dan Loyalitas Pasien Rawat Jalan (Studi pada Rumah Sakit Ibu dan Anak PKU Muhammadiyah Cipondoh, Tangerang) - Nurmiwiyati Nurmiwiyati; Amelia Oktrivina DS; MGS Aritonang; Kosasih Kosasih (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Customer satisfaction is the key to creating customer loyalty, as well as in-hospital services. This study will examine aspects of drug availability and quality of service and its effect on the satisfaction and loyalty of outpatients at PKU Muhammadiyah Hospital in Cipondok, Tangerang. This study uses a survey method with a questionnaire as a data collection tool. A quantitative approach was carried out using Structural Equation Modeling (SEM) analysis with LISREL. The study sample was taken from all patients who visited the outpatient unit at PKU Muhammadiyah Hospital in Cipondoh, Tangerang, or their families who came for treatment and bought medicine at PKU Muhammadiyah Hospital in Cipondoh, Tangerang. The results showed Availability of drugs had a significant effect on outpatient satisfaction, The quality of pharmaceutical installation services has a significant effect on outpatient satisfaction, Availability of drugs significantly influences outpatient loyalty, Service quality has no significant effect on outpatient loyalty, and patient satisfaction has a significant effect on outpatient loyalty. The results of statistical tests noted that 86% of patient satisfaction levels were affected by the availability of drugs and the quality of services, and 89% of patient loyalty was influenced by the availability of drugs and quality of service.